Style Translation in an English Version of Tunisian Mustapha Tlili’s novel The Lion Mountain: A Cognitive Basis to Assessment - Khalid Majhad; Chakib Bnini; Mohammed Kandoussi (Yayasan Visi Intan Permata, 2019)
Style is every literary author’s identity marker. No translation can ever claim success if it does not reflect the marked stylistic features of the original. This paper assesses the English translation of Tunisian Mustapha Tlili’s novel Lion Mountain in terms of its reproduction of the spirit of the source text, that is the totality of effects generated by the author’s stylistic manners. A cognitive basis to assessment means that the author’s style is a direct expression of his state of mind, his attitudes and beliefs. This model, inspired by the work of Chinese translator and theorist Jin Di (2003), uses a hermeneutic four-stage analysis of literary texts (i.e. penetration, acquisition, transition and presentation), that makes it possible to deal in a rather systematic manner with every aspect of the literary text, namely its spirit, substance, overtone, flavor and imagery. The assessment will demonstrate how translating successes or failures result directly from successes or failures in applying one or more of these hermeneutics-inspired four stages.